Sarcopenia is associated with incident albuminuria in patients with type 2 diabetes: A retrospective observational study. Issue 6 (30th March 2017) - Bouchi, Ryotaro; Fukuda, Tatsuya; Takeuchi, Takato; Minami, Isao; Yoshimoto, Takanobu; Ogawa, Yoshihiro
Abstract : Our results showed that sarcopenia is an important determinant of both progression and regression of albuminuria in Japanese patients with type 2 diabetes. Abstract: Sarcopenia, defined as age‐related loss of skeletal muscle mass and function, increases the risk of albuminuria. However, it has still unknown whether sarcopenia could increase the risk for the progression of albuminuria. A total 238 patients with type 2 diabetes (mean age 64 ± 12 years; 39.2% women) were studied in the present retrospective observational study. The prevalence of sarcopenia was 17.6%. During the median follow‐up period of 2.6 years, albuminuria was measured 5.8 ± 1.8 times, and progression of albuminuria was observed in 14.9% of patients with normoalbuminuria, as was 11.5% in those with microalbuminuria. Sarcopenia was significantly associated with both progression (hazard ratio 2.61, 95% confidence interval 1.08–6.31, P = 0.034) and regression (hazard ratio 0.23, 95% confidence interval 0.05–0.98, P = 0.048) of albuminuria by multivariate Cox regression analysis. The present data suggest that sarcopenia is an important determinant of both progression and regression of albuminuria in patients with type 2 diabetes.